Towards Authentic Transformational Leadership of Emergency Management Systems - Caro, Denis H. J. (Université d'Ottawa | University of Ottawa, 2015)
In this 21st century of unprecedented global, national and regional threats and innovative technologies, this study underscores the unique authentic transformational leadership challenges posed in emergency management systems. These open complex systems adapt to a range of critical emergency events, including mass emergencies, disasters and catastrophes. This qualitative research study based on grounded theory examines the phenomenology of emergency management systems by deploying triangulation to isolate the particular theoretical underpinnings of authentic transformational leadership models relevant to this domain. Using a key informant approach and a semi-structured confidential questionnaire, the perspectives of 103 emergency, health care and technological leaders of diverse professional backgrounds on the challenges of emergency management systems are presented. The response rate was 83.5 percent from 81 organizations across Canada. This study underscores the need for authentic transformational leadership and identifies seven critical and specific leadership imperatives for this domain. The implications for hospital and health care administrators are also presented. This qualitative study of diverse emergency system leaders is original in that it has not hitherto been done across Canada nor internationally. This study underscores the relevance of leadership theory and principles in the extant literature, but extends this to highlight those that are critical and unique to leaders of emergency management systems. In so doing, calls on the need for authentic transformation leadership of an order and caliber yet to be fully potentiated to manage future emergency events in Canada.